Efficacy of Benzocaine and Lidocaine Bioadhesive Patches in Various Minor Oral Surgical Procedures in Children - An Evaluative Study - Nisha E. John; Ramakrishnan Erakkodan; Natta Sreelakshmi (Indian Journal of Dental Research)
Context: The key to successful management of a child in the dental clinic depends greatly on providing painless anaesthesia. Topical anaesthesia using bioadhesive patches may be a breakthrough in this field. Aims: The purpose of the study was to compare the efficacy of Benzocaine and Lidocaine bioadhesive patches in reducing pain associated with various minor oral surgical procedures in children. Methods and Materials: Hundred subjects, aged 6–9 years, requiring various minor oral surgical procedures such as extractions of primary teeth, nerve blocks, mucocele excision or drainage of abscesses were divided equally into Groups 1 and 2. In Group 1, custom fabricated Benzocaine patches were placed for 5 minutes at the target site prior to the procedure, and in Group 2, Lidocaine patches were used in the same manner. Each subject completed a visual analogue scale (VAS) and Wong-Baker Faces pain scale (FPS) after each procedure. Pulse rate and saturation of peripheral oxygen were assessed using pulse oximeter. The duration of the study was from September 2014 to September 2015. Statistical Analysis Used: The statistical analysis was done using paired t test, ANOVA and Bonferroni post hoc analysis. P value less than 0.05 were considered as statistically significant. Results: A significant difference in pain scores was observed favouring the use of Benzocaine over Lidocaine patches (P < 0.05). However, no significant differences in pulse oximeter readings were observed. Conclusions: A statistically significant reduction in pain rating scores was observed in the Benzocaine group after a five-minute application of the patch.